Analisis Positioning Dan Brand Image Terhadap Keputusan Pelanggan Perusahaan Ekspedisi : Studi Kasus Perusahaan Lalamove - Ridwan Setya Nugraha (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Lalamove is an Asia-based technology company that provides delivery services by connecting users with delivery drivers through web applications and mobile devices. The development of a company depends on how the ability to win the competition. To win the competition, it is necessary to have the right strategy in conducting marketing so that it can attract buying interest. Positioning is the company's actions to design products that are superior to other similar products in order to create a good impression in the minds of consumers. Meanwhile Brand Image is a representation of every overall perception of the brand. Because a brand allows it to influence consumers in making purchases and carry the good name of companies that produce goods or services. This study aims to determine and analyze the relationship between positioning and brand image on purchasing decisions. The method used is quantitative. Subjects in this study involved 30 people. The data collection method uses three scales, customer decision scale, positioning scale, and brand image scale. Research sampling using purposive sampling. The data were analyzed using the regression model and the model was gradually filled in with the help of the SPSS for Windows Statistical Package for Social Sciences program.